Comparing the long-term outcomes in chronic coronary syndrome patients with prior ST-segment and non-ST-segment elevation myocardial infarction: findings from the TIGRIS registry - Satoshi Yasuda; Christopher B Granger; David B Brieger; Shaun G Goodman; Tabassome Simon; Dirk Westermann; Stuart Pocock; Ruth Owen; Mauricio G Cohen; Karolina Andersson; Prashant Kaul; Jose Carlos Nicolau; et al. (BMJ Open)
Objectives Compared with ST-segment elevation myocardial infarction (STEMI) patients, non-STEMI (NSTEMI) patients have more comorbidities and extensive coronary artery disease. Contemporary comparative data on the long-term prognosis of stable post-myocardial infarction subtypes are needed.Design Long-Term rIsk, clinical manaGement and healthcare Resource utilisation of stable coronary artery dISease (TIGRIS) was a multinational, observational and longitudinal cohort study.Setting Patients were enrolled from 350 centres, with >95% coming from cardiology practices across 24 countries, from 19 June 2013 to 31 March 2017.Participants This study enrolled 8277 stable patients 1–3 years after myocardial infarction with ≥1 additional risk factor.Outcome measures Over a 2 year follow-up, cardiovascular events and deaths and self-reported health using the EuroQol 5-dimension questionnaire score were recorded. Relative risk of clinical events and health resource utilisation in STEMI and NSTEMI patients were compared using multivariable Poisson regression models, adjusting for prognostically relevant patient factors.Results Of 7752 patients with known myocardial infarction type, 46% had NSTEMI; NSTEMI patients were older with more comorbidities than STEMI patients. NSTEMI patients had significantly poorer self-reported health and lower prevalence of dual antiplatelet therapy at hospital discharge and at enrolment 1–3 years later. NSTEMI patients had a higher incidence of combined myocardial infarction, stroke and cardiovascular death (5.6% vs 3.9%, p<0.001) and higher all-cause mortality (4.2% vs 2.6%, p<0.001) compared with STEMI patients. Risks were attenuated after adjusting for other patient characteristics. Health resource utilisation was higher in NSTEMI patients, although STEMI patients had more cardiologist visits.Conclusions Post-NSTEMI chronic coronary syndrome patients had a less favourable risk factor profile, poorer self-reported health and more adverse cardiovascular events during long-term follow-up than individuals post STEMI. Efforts are needed to recognise the risks of stable patients after NSTEMI and optimise secondary prevention and care.Trial registration number NCT01866904.